Challenges for a Better Fire Management in South America - Moura, Livia Carvalho; Pivello, Vânia R.; Berlinck, Christian Niel; Schmidt, Isabel Belloni; Fidelis, Alessandra [UNESP] (Springer Nature, 2025)
The use of fire as a management tool by South American Indigenous Peoples is highly connected to their traditional knowledge, culture and governance, serving purposes like landscape management, subsistence agriculture, hunting, cultural rituals and fruiting stimulation. Despite this, many countries worldwide, influenced by European colonialism, adopted zero-fire policies, focused on fire suppression. These command-and-control policies that simply prohibit and criminalize fire tend to be ineffective in fire-prone ecosystems and where local traditions include fire for land management. Instead of inhibiting fires, the zero-fire policy ended up promoting large wildfires, arson, conflicts, socioeconomic problems, cultural loss and environmental degradation. Alternatively, more adequate, adaptive and participatory policies have increasingly replaced fire suppression, with noticeable results. After long processes of discussion and political persuasion, the Integrated Fire Management approach, that combines techniques and knowledge from different stakeholders, has been implemented in countries like Colombia, Ecuador, Paraguay and Brazil with positive outcomes. However, challenges remain, including the lack of engagement and investment from the private sector, conflicts with political agendas and the absence of state regulations. To improve fire management and achieve long term success, policies should adopt participatory and intercultural approaches, integrate knowledge and emerging technologies, also encourage local, national and international collaborations.